Aromatic sulfonate anion-induced pseudorotaxanes: environmentally benign synthesis, selectivity, and structural characterization. Issue 10 (27th November 2014) - Gong, Han-Yuan; Tang, Feng; Rambo, Brett M.; Cao, Rui; Xiang, Jun-Feng; Sessler, Jonathan L.
Abstract : Aromatic sulfonates allow the effective construction of anion-containing pseudorotaxanes from a tetracationic macrocycle known as the "Texas box" in organic media and under organic-free aqueous conditions. Abstract : Anion-induced molecular threading is an emerging strategy for generating mechanically interlocked molecular architectures. Herein, we report the preparation of two pseudorotaxane structures generated from aromatic sulfonate anions and a tetraimidazolium-containing macrocycle in organic media, as well as under environmentally benign aqueous conditions.